1, 25(OH)2D3 protects β cell against high glucose-induced apoptosis through mTOR suppressing. (15th October 2015) - Yang, Zesong; Liu, Fang; Qu, Hua; Wang, Hang; Xiao, Xiaoqiu; Deng, Huacong
Abstract: Diabetes mellitus is a leading cause of death and disability worldwide, which presents a serious public health crisis in China nowadays. It has been well recognized that excessive β-cell apoptosis is the key pathogenesis of diabetes, of which the mammalian target of rapamycin (mTOR) serves as the critical signaling pathway. Emerging evidence indicates that vitamin D deficiency acts as a potential risk factor for diabetes. The present study aims to test the hypothesis that 1 alpha, 25-dihydroxyvitamin D(3) [1, 25(OH)2 D3 ] can inhibit β-cell apoptosis via the suppression of mTOR signaling pathway. β-cells (INS-1) were cultured in the context of normal glucose or high glucose media with or without 1, 25(OH)2 D3 treatment. β-cell apoptosis was evaluated by inverted fluorescence microscope, flow cytometry and electron microscope, respectively. Quantitative RT-PCR and Western blotting were performed to assess the possible perturbations in mTOR signaling pathway. High glucose significantly increased β-cell apoptosis. Of importance, RT-PCR and Western blotting demonstrated that high glucose inhibited DNA-damage-inducible transcript 4 (DDIT4) and TSC1/TSC2, up-regulated Rheb/mTOR/p70S6K and enhanced expression of the apoptosis regulating proteins, such as phospho-Bcl-2, cytochrome C and cleaved caspase. Interestingly, 1, 25(OH)2 D3 treatment reversed high glucose induced pathological changes in mTOR signaling pathway, restored expression of DDIT4 and TSC1/TSC2, blocked aberrant up-regulation of Rheb/mTOR/p70S6K and the apoptosis regulating proteins, and effectively inhibited β-cell apoptosis. Therefore, 1, 25(OH)2 D3 treatment can effectively protects β cell against high glucose-induced apoptosis mainly via the suppression of mTOR signaling pathway, which may be considered as a potential therapy for patients with diabetes. Highlights: High glucose significantly increased β-cell apoptosis. 1, 25(OH)2 D3 treatment effectively protects β cell against high glucose-induced apoptosis through mTOR suppressing. 1, 25(OH)2 D3 serves as a potential therapy for patients with diabetes.